PEMILIHAN TIPE PEMBANGKIT LISTRIK TENAGA GELOMBANG LAUT TIPE PELAMPUNG DI PANTAI SALUBOMBA KABUPATEN DONGGALA - Setiyawan Setiawan; Yuli Asmi Rahman; Muhammad Sarjan; Nurhani Amin (Foristek, 2021)
Indonesia is a country that has an area of sea three times larger than the land area. In line with the rapid development, the need for electricity is also increasing. So that Indonesia has great potential to produce alternative and environmentally friendly energy, namely Sea Wave Energy. Its continuous nature is available all the time. Many potential coastal areas in Indonesia, however, have not been utilized optimally. The purpose of this study is to see the potential of Wave Energy for electricity. For this reason, research was carried out at a location in the Central Sulawesi area, precisely in Salubomba, Central Banawa District, Donggala Regency. In this study a potential study was conducted on 3 types of PLTGL, namely Buoy, OWC, and Pasut Dam, where one will be chosen that meets the wave criteria requirements on the Beach. From the results of research, PLTGL that fulfills the requirements is the type of buoy. Data collection begins with secondary data, namely wind data from Mutiara Station. Then proceed with calculating wave forecasting using the SMB (Sverdrup Munk-Bretschneider) method. The results of this study, Salubomba beach has the potential to be built by the Buoy Type Wave Power Plant, a significant wave height of 0.52 - 3.37 meters with a ruptured depth of 3.95 meters.